Distribution and genetic structure of Aedes japonicus japonicus populations (Diptera: Culicidae) in Germany - Huber, Katrin; Schuldt, Kathrin; Rudolf, Martin; Marklewitz, Marco; Fonseca, Dina M.; Kaufmann, Christian; Tsuda, Yoshio; Junglen, Sandra; Krüger, Andreas; Becker, Norbert; Tannich, Egbert; Becker, Stefanie C. (Parasitology research, 2014)
In recent years, the number of imported cases of arthropod-borne diseases in Europe, such as dengue fever, has increased steadily, as did the emergence and distribution of invasive insect vectors. Consequently, the risk of disease spreading into previously unaffected regions through invasive mosquitoes is also increasing. One example of an invasive mosquito is Aedes japonicus japonicus (A. j. japonicus), which spread from its original habitat in Japan to North America and Europe. This species has been shown to act as a vector for Japanese encephalitis and West Nile viruses. In Europe, A. j. japonicus has been detected in Switzerland, Belgium, Slovenia, and Germany, where it has become a resident species. Here, we describe the recent spread and genetic structure of A. j. japonicus populations in Germany. By monitoring the species in Baden-Württemberg in 2011 and 2012, we observed a considerable enlargement of the infested area from 54 municipalities in 2011 to 124 municipalities in 2012. To elucidate the colonization of Europe by A. j. japonicus, seven microsatellite loci were studied in 106 individuals sampled in Germany and Switzerland in 2012. The same markers were genotyped in 31 North American and 26 Japanese specimens. Population genetic analyses indicated that A. j. japonicus in Baden-Württemberg and North Rhine-Westphalia represented two genetically distinct populations with FST—values of 0.073-0.152, suggesting that they originated from two independent introduction events in the past. These results are of particular interest in light of vectorial variability for the transmission of viruses and other pathogens in Europe.
Gesehen am 18.09.2020